Çalışan Deneyimi: İnsan Kaynakları Yönetimi Fonksiyonları Bağlamında Bir Sentez - Aksakal, Nihan Yavuz (Fırat University, 2026)
Günümüzde birçok alanda olduğu gibi insan kaynakları yönetimi alanında da değişimler yaşanmaktadır. Stratejik insan kaynakları yönetimine geçiş, rekabet açısından insan kaynağının öneminin artması, teknolojik gelişmeler, modern yönetim teknikleri gibi farklı konularda yaşanan değişimler işletmeler bağlamında yeni kavramları da beraberinde getirmektedir. Bu kavramlardan biri de çalışan deneyimidir. Bir bireyin organizasyonla ilgili tüm deneyimleri ve sahip olduğu algıyı ifade eden çalışan deneyimi, çalışanı odak noktasına alan bir yaklaşım sergilemektedir. Bu çalışmanın amacı; çalışan deneyiminin ortaya çıkmasına katkı sağlayan teorik düşünceleri açıklamak, insan kaynakları yönetimi ve fonksiyonları bağlamında çalışan deneyimi kavramını ele almaktır. Çalışma, kavramsal bir inceleme makalesi olup, kavramı çeşitli yönlerden inceleyerek insan kaynakları yönetimi alanına katkı sağlamayı amaçlamaktadır. Olumlu bir çalışan deneyimi yaratabilmek için çalışanı odak noktasına alacak şekilde organizasyona bütünsel bir bakış açısıyla yaklaşılması ve tüm uygulamalarda çalışan deneyimi geliştirme odaklı çalışmalar yapılması önemli görülmektedir. Böylece olumlu çalışan deneyiminin yaratılabildiği organizasyonlar sadece iş yapılan yerler olarak görülmekten çıkıp, çalışanların değer gördüğü bir yer haline dönüşmektedir.

As in many areas today, changes are taking place in the field of human resources management. Changes in different areas such as the transition to strategic human resources management, the increasing importance of human resources in terms of competition, technological developments, and modern management techniques bring new concepts with them in the context of businesses. One of these concepts is employee experience. The employee experience, which expresses all the experiences of an individual related to the organization and the perception he has, demonstrates an approach that puts the employee in the focus. The aim of this study is to express the theories that are thought to contribute to the concept of employee experience, to address the concept in a manner and within the framework of functions related to human resources management. The study is a conceptual review article and is designed with a qualitative research design. The study aims to contribute to the field of human resources management by examining the concept from various aspects. According to the results of the study, in order to create a positive employee experience, a holistic perspective focused on employees and studies on employee experience in all applications are deemed important. It is necessary to understand their needs and expectations from the organization, to adopt horizontal harmony in human resources practices and strategies, to pay attention to the communication process between subordinates and superiors, to integrate technology and digitalization into business processes, and to be able to design employee-focused applications. By creating a positive employee experience, organizations become places where employees are valued rather than just places where work is done
Employee Experience: A Synthesis in the Context of Human Resources Management Functions
Keywords: Industrial and Organisational Psychology (Incl. Human Factors); Endüstriyel ve Örgütsel Psikoloji (İnsan Faktörleri Dahil)